STRATEGI START-UP PRODUKSI BIOGAS DARI CAMPURAN SAMPAH BUAH DENGAN MENGGUNAKAN STARTER KOTORAN SAPI : HASIL PERCOBAAN MENGGUNAKAN CAMPURAN SAMPAH BUAH SAMPAI DENGAN 10 PERSEN - , RAHMIAH SJAFRUDDIN, ST, Ir. Siti Syamsiah Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Biogas is a renewable energy which can be considered as an alternative energy that can subtitute fosil fuel. Utilizing fruit waste to produce biogas can reduce the consumtion of comercial energy source such as fosil fuel and reduce waste accumulation as well. Biogas is produced through organics-compoundcracking- process which employe anaerob microorganism within a biodigester. The production process of biogas follows three steps i.e, hydrolisis,acydogenesis, and methanogenesis. Several factors affect the production process of biogas i.e, substrates, operating (environment) condition and microorganisms. The fruit waste contains high organics compounds, so it is potential to be the raw material of biogas. However, fruit waste has several characteristics such as low pH 4-6, lack of methanogen organism, and contains chemicals which could inhibitor biogas production, such as limonen in orange and tannin in apples. Thus, a certain strategy is needed in the utilizing fruit waste to produce biogas especially in the step of start up. The purpose of this research is to get strategy of start up and aclimation process which suitable to the production process of biogas in fruit waste in a continous biodigester. The biodigester is operated in continous process with the loading rate of 2kg/day and the operating capacity of 36 kg. Biodigester is equipped with an inlet channel, outlet of slurry, agitator, manometer, and gas holder. Start up strategy is done by feeding the biodigester with 100% cow menure and then the manure is replaced with mixed fruit waste gradually. Result of this reseach show mireasing percentage of fruit waste in the input (up to 10% of fruit waste) increase production of gas. However, the methane concentration is relative constant (Â± 50). The production of biogas and methane level is not affected by the change of fruit waste which has low of pH level. Have an inhibitor with gradual operating condition.